2014
DOI: 10.1039/c4ee01850h
|View full text |Cite
|
Sign up to set email alerts
|

Large scale, flexible and three-dimensional quasi-ordered aluminum nanospikes for thin film photovoltaics with omnidirectional light trapping and optimized electrical design

Abstract: Optimized nanospiked solar cell achieved efficiency of 7.92 % which is among the highest on a flexible substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 61 publications
0
36
0
Order By: Relevance
“…A similar phenomenon has also been reported in previous literature due to the solvent loss . Thin‐film a ‐Si:H solar cells are fabricated on the patterned 3D substrates and detailed fabrication processes of the solar cells can be found in our previous work . The photographs of solar cells on both patterned and flat substrates are shown in Supporting Information Figure S2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar phenomenon has also been reported in previous literature due to the solvent loss . Thin‐film a ‐Si:H solar cells are fabricated on the patterned 3D substrates and detailed fabrication processes of the solar cells can be found in our previous work . The photographs of solar cells on both patterned and flat substrates are shown in Supporting Information Figure S2.…”
Section: Resultsmentioning
confidence: 99%
“…Sai and co‐workers have demonstrated hydrogenated microcrystalline silicon (µc‐Si:H) single‐junction and tandem solar cells based on the textured flexible aluminum (Al) foils . Independently, we reported a number of thin film amorphous silicon ( a ‐Si:H) solar cells built on flexible Al foils with tunable nanostructures . Utilizing the cost‐effective electrochemical anodization process, a variety of three‐dimensional (3‐D) back reflectors with precisely controlled pitch and height (or depth) have been realized with distinctly improved broadband absorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of multiscale design is also evident from ecological studies that show that forests with a diverse flora spanning a range of heights, and hence constituting a multiscale canopy, lead to a very efficient interception of sunlight, thus offering another biological motivation to hierarchical structuring . In the area of optoelectronic design, however, most of the literature till date is focused on the effects of a single level of patterning such as continuous nanostructured arrays for light confinement in the context of solid‐state photovoltaics, to maximize the absorption of light per unit device area. The main goal of this design is to obtain a complete nanostructural coverage over the device area to maximize light trapping and absorption.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades, numerous efforts have been dedicated to improve the broadband optical performance by designing the state‐of‐the‐art light harvesting structures. It has been revealed that 3D nanostructured antireflection (AR) films and back‐reflective structures, such as commercial Asahi‐U‐type textured substrates, nanodots, nanocones, inverted nanocones, nanodents, nanospikes, etc., can substantially boost the PCE performance via various light trapping mechanisms . In practical application of solar panels, the incident angle of solar irradiation changes over time in a day.…”
mentioning
confidence: 99%